The agroecosystems diagnosis of the Mariana Hydrographic Microbasin in the Amazonia Portal Territory, Mato Grosso State, Brazil - Roboredo, Delmonte; Bergamasco, Sonia Maria Pessoa Pereira; Gervázio, Wagner (Sustainability in Debate, 2017)
The opening of new agricultural frontiers in the 70s, as it happened in Alta Floresta, Mato Grosso, was stimulated by the federal government and took place without any concern for the preservation of forests, thus contributing to the generation of strong negative externalities. This work aims to carry out a socioenvironmental diagnosis of the Mariana Hydrographic Microbasin of the municipality of Alta Floresta, in the Mato Grosso State of Brazil. The systemic approach employed for this research included the use of semi-structured interviews and the soil physical analysis.. Results indicate that 78.6% of respondents had bought their properties in the 80/90s. Of that percentage, 84% respondents reported that they had not received any orientation regarding the preservation of riparian forests, and 93% answered that while they did had an interest in recovering degraded areas, they lacked the necessary financial resources to implement such a recovery. The study also points out the social and environmental degradation of the territory, showing, among other indicators, that 74.5% of the soils of the researched agroecosystems presented macroporosity of less than 10%; a marked lack of social participation, and a strong flow of rural migration that compromises the possibility of social reproduction.